Association between process measures and mortality in individuals with opioid use disorders. (1st August 2017) - Watkins, Katherine E.; Paddock, Susan M.; Hudson, Teresa J.; Ounpraseuth, Songthip; Schrader, Amy M.; Hepner, Kimberly A.; Stein, Bradley D.
Highlights: Better quality is associated with lower mortality in people with opioid disorders. By improving quality, health systems may reduce avoidable excess mortality. Avoiding unnecessary prescription opioids and benzodiazepines is a prime target. Psychosocial treatment and treatment continuity is associated with lower mortality. Abstract: Background: Individuals with opioid use disorders have high rates of mortality relative to the general population. The relationship between treatment process and mortality is unknown. Aim: To examine the association between 7 process measures and 12- and 24-month mortality. Methods: Retrospective cohort study of patients with opioid use disorders who received care from the Veterans Administration between October 2006 and September 2007. Logistic regression models were used to examine the association between 12 and 24-month mortality and 7 patient-level process measures, while risk-adjusting for patient characteristics. Process measures included quarterly physician visits, any opioid use disorder pharmacotherapy, continuous pharmacotherapy, psychosocial treatment, Hepatitis B/C and HIV screening, and no prescriptions for benzodiazepines or opioids. We conducted sensitivity analyses to examine the robustness of our findings to an unobserved confounder. Results: Among individuals with opioid use disorders, not being prescribed opioids or benzodiazepines, receipt of any psychosocial treatment and quarterly physician visits were significantly associated with lower mortality at both 12 and 24 months, but Hepatitis and HIV screening, and measures related to opioid use disorder pharmacotherapy were not. Sensitivity analyses indicated that the difference in the prevalence of an unobserved confounder would have to be unrealistically large given the observed data, or there would need to be a large effect of the confounder, to render these findings non-significant. Conclusions and relevance: This is the first study to show an association between process measures and mortality in patients with opioid use disorders and provides initial evidence for their use as quality measures.